Diagnostic strategies for SARS-CoV-2 infection and interpretation of microbiological results. (September 2020) - Caruana, G.; Croxatto, A.; Coste, A.T.; Opota, O.; Lamoth, F.; Jaton, K.; Greub, G.
Abstract: Background: To face the current COVID-19 pandemic, diagnostic tools are essential. It is recommended to use real-time RT-PCR for RNA viruses in order (a) to perform a rapid and accurate diagnostic, (b) to guide patient care and management and (c) to guide epidemiological strategies. Further studies are warranted to define the role of serological diagnosis and a possible correlation between serological response and prognosis. Objectives: The aim was to guide clinical microbiologists in the use of these diagnostic tests and clinicians in the interpretation of their results. Sources: A search of literature was performed through PubMed and Google Scholar using the keywords SARS-CoV-2, SARS-CoV-2 molecular diagnosis, SARS-CoV-2 immune response, SARS-CoV-2 serology/antibody testing, coronavirus diagnosis. Content: The present review discusses performances, limitations and use of current and future diagnostic tests for SARS-CoV-2. Implications: Real-time RT-PCR remains the reference method for diagnosis of SARS-CoV-2 infection. On the other hand, notwithstanding its varying sensitivity according to the time of infection, serology represents a valid asset (a) to try to solve possible discrepancies between a highly suggestive clinical and radiological presentation and negative RT-PCR, (b) to solve discrepancies between different PCR assays and (c) for epidemiological purposes.